2021
DOI: 10.1155/2021/6684770
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide/Gold Nanoparticles Modified Screen‐Printed Electrode for the Determination of Palmitic Acid

Abstract: Palm oil is one of the major oils and fats produced in the world today. The quality of palm oil is crucial to be investigated, and one of the quality indices is free fatty acid (FFA) content. Therefore, in this study, an electrochemical approach for the determination of FFA has been explored as an alternative to replace the conventional method (titration method). The electrochemical method was developed based on electrochemically reduced graphene oxide (rGO) coupled with gold nanoparticles (AuNPs) deposited on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The DPV peak current values for AuNPs/Gr, AuNPs, and Gr electrode surfaces were 31.55, 26.36, and 26.21 mA, respectively. This finding proves that the AuNPs/Gr nanocomposite is suitable for electrochemical analysis and enhances the electrocatalytic activity by facilitating electron transfer in the redox process [54].…”
Section: Electrochemical Characterisation Of Screen-printed Carbon El...supporting
confidence: 56%
“…The DPV peak current values for AuNPs/Gr, AuNPs, and Gr electrode surfaces were 31.55, 26.36, and 26.21 mA, respectively. This finding proves that the AuNPs/Gr nanocomposite is suitable for electrochemical analysis and enhances the electrocatalytic activity by facilitating electron transfer in the redox process [54].…”
Section: Electrochemical Characterisation Of Screen-printed Carbon El...supporting
confidence: 56%
“…3a), demonstrating the successful reduction of Go into rGo. 30 Figure 3c shows AuNPs distributed on the rGo film, it can be observed that the surface particles are attached, with a large number of evenly dispersed AuNPs densely distributed on the surface of rGo, with little aggregation. Further characterization of the electrochemical properties of different electrodes was carried CV.…”
Section: Resultsmentioning
confidence: 96%
“…These results were compatible with earlier reports. [31][32][33][34][35][36][37] In order to see the effect of ctdsDNA concentration upon the response of biosensor, ctdsDNA in various concentrations from 10 to 70 μg ml −1 was immobilized onto the surface of CA-GO-PGE, and accordingly the changes at the oxidation and reduction signals of [Fe(CN) 6 ] 3−/4− was examined by CV (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%